2023
DOI: 10.1134/s0006297923070076
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Methionine Addiction of Cancer Cells with Methioninase

Abstract: All types of cancer cells are addicted to methionine, which is known as the Hoffman effect. Restricting methionine inhibits the growth and proliferation of all tested types of cancer cells, leaving normal cells unaffected. Targeting methionine addiction with methioninase (METase), either alone or in combination with common cancer chemotherapy drugs, has been shown as an effective and safe therapy in various types of cancer cells and animal cancer models. About six years ago, recombinant METase (rMETase) was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The present study suggests that methionine restriction is promising in combination with second-line chemotherapy for metastatic breast cancer and further clinical studies are needed. o-rMETase is effective as it targets the fundamental basis of cancer, methionine addiction (6)(7)(8)(9)(10)(11)(12)(13)(14)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…The present study suggests that methionine restriction is promising in combination with second-line chemotherapy for metastatic breast cancer and further clinical studies are needed. o-rMETase is effective as it targets the fundamental basis of cancer, methionine addiction (6)(7)(8)(9)(10)(11)(12)(13)(14)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…The present study indicates the possibility of reducing the dose of IRN, without attenuating its efficacy, by combining it with rMETase, and provides an improved therapeutic opportunity for patients with colon cancer. rMETase is effective since it targets the fundamental and general hallmark of cancer, methionine addiction (6)(7)(8)(9)(10)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…However, tumor cells are incapable of utilizing Hcy to synthesize Met for several reasons, with the leading cause being the ineffectiveness of the Met synthase enzyme in cancer cells. Thus, tumor cells are more sensitive to the MR environment [60,[62][63][64]. Nevertheless, our comprehension of the role of Met metabolism in cancer remains at an early stage due to its intricate nature.…”
Section: Mechanisms Of Met In the Pathophysiology Of Gastric Cancermentioning
confidence: 99%
“…Thus, in theory, MR could augment the efficacy of chemotherapeutic drugs for treating cancer. A growing body of research has demonstrated that MR can synergistically interact with various chemotherapeutic agents; for instance, cancer cells in Met − /Hcy+ medium selectively arrested in the S/G2 phase and furthermore eliminated clonogenic cells and rendered cancer cells sensitive to cell-cycle-specific drugs [64], including 5-fluorouracil [136], gemcitabine [137], cisplatinum [52], Doxorubicin (DOX), Vincristine (VCR) [138], and so on. In addition to inducing the chemo-sensitive S/G2 phase, MR has the potential to augment the efficacy of chemotherapeutic agents through alternative pathways.…”
Section: The Role and Mechanism Of Met In Gastric Cancer Chemotherapymentioning
confidence: 99%